The development of novice top management team's heuristics in SME internationalization - Niittymies, Aleksi (2016)
The importance of heuristics in terms of strategy work is highlighted in many existing studies. However, little is known about how the ability to utilize heuristics develops during novice top management team’s first internationalization. Utilizing qualitative and inductive grounded theory building methods this study aims to increase knowledge about the role of heuristics during top management team’s first SME internationalization and the role of experience in utilization of heuristics and decision-making process. The findings contribute to literature of strategy and its microfoundations by showing four stages of development process and highlighting the various roles of relevant experience in the process. The findings increase understanding of heuristics affecting managers’ decision-making and the experience’s impact on the heuristics in context of SME internationalization.